The Dimensions of Morality of Modern Rule of Law - Zhu, Qianqian (Journal of Theory and Practice of Management Science, 2024)
The rule of law is a civilized order, and the concept of the rule of law has been widely accepted by people. The relationship between the rule of law and morality has always been a difficult issue in the theory of rule of law. This article combs the historical origins of modern rule of law, summarizes the main contents of modern rule of law, and analyzes the moral dimension of modern rule of law. In the construction of the rule of law in China, we should be particularly vigilant about the risks of the separation of the rule of law from morality.